Eligibility for PCSK9 treatment in 734 Hypercholesterolemic patients referred to a regional cholesterol treatment center with LDL cholesterol ≥70 mg/dl despite maximal tolerated cholesterol lowering therapy. Issue 1 (December 2016) - Glueck, Charles; Shah, Parth; Goldenberg, Naila; Prince, Marloe; Lee, Kevin; Jetty, Vybhav; Kumar, Ashwin; Goldenberg, Michael; Wang, Ping
Abstract Background LDL cholesterol (LDLC) lowering has been revolutionized by PCSK9 inhibitors, Alirocumab (Praluent) and Evolocumab (Repatha), approved as adjuncts to maximally tolerated cholesterol lowering therapy in heterozygous (HeFH) or homozygous (HoFH) familial hypercholesterolemia, and/or clinical atherosclerotic cardiovascular disease (CVD) where LDLC lowering is insufficient. Methods We applied FDA and insurance eligibility criteria for PCSK9 inhibitor use in 734 hypercholesterolemic patients serially referred over 3 years who then received ≥ 2 months maximally tolerated LDLC lowering therapy with follow up LDLC ≥ 70 mg/dl, and in 50 patients approved by insurance for PCSK9 inhibitors. We documented the percentage of patients with HeFH and/or CVD who met FDA and insurance criteria for PCSK9 inhibitor therapy using LDLC goal-based guidelines. Results Of 734 patients with LDLC ≥ 70 mg/dl after ≥ 2 months maximally tolerated LDLC lowering therapy, 220 (30 %) had HeFH and/or CVD with LDLC > 100 mg/dl, meeting FDA-insurance criteria for PCSK9 inhibitor therapy. Another 66 (9 %) patients were statin intolerant, without HeFH or CVD. Of the 50 patients whose PCSK9 inhibitor therapy was approved for insurance coverage, 45 (90 %) had LDLC > 100 mg/dl after ≥ 2 months on maximally tolerated LDLC lowering therapy. Seventeen of these 50 patients (34 %) had HeFH without CVD (LDLC on treatment 180 ± 50 mg/dl), 15 (30 %) had CVD without HeFH (LDLC on treatment 124 ± 26 mg/dl), 14 (28 %) had both HeFH and CVD (LDLC on treatment 190 ± 53 mg/dl), and 4 (8 %) had neither HeFH nor CVD (LCLC 142 ± 11 mg/dl). Conclusion Of 734 patients referred for LDLC reduction, with LDLC ≥ 70 mg/dl after ≥ 2 months on maximally tolerated therapy, 220 (30 %) had HeFH and/or CVD with LDLC > 100 mg/dl, meeting FDA-insurance criteria for PCSK9 inhibitor therapy as an adjunct to diet-maximally tolerated cholesterol lowering therapy in HeFH or CVD. If 30 % of patients with high LDLC and HeFH-CVD are eligible for PCSK9 inhibitors, then specialty pharmaceutical pricing models ( 14, 300/year) will collide with tens of millions of HeFH-CVD patients. We speculate that if there was a 50 % reduction in CVD, then there would be savings of 245 billion, in the middle of the range of estimated PCSK9 inhibitor costs of 185-342 billion. Whether the health care savings arising from the anticipated reduction of CVD events by PCSK9 inhibitors justify their extraordinary costs in broad population use remains to be determined.